European banks and tax havens: Evidence from country-by-country reporting - Petr Jansky (Charles University in Prague, Institute of Economic Studies (IES), 2018)
Banks in the European Union recently started publicly reporting data on profit, number of employees, turnover and tax on a country-by-country basis. I introduce the largest, hand-collected data set of its kind, which covers almost 50 banks for up to 5 years between 2013 and 2017. I identify the main locations of European bank's profits, which include the largest European economies as well as tax havens. I focus on answering the question of how geographically aligned these profits are with economic activity. I find that some of the tax havens have maintained high shares of profits in contrast with their much lower shares of employees. These results indicate that banks are likely shifting their profits to tax havens, but for the profit shifting to be directly observed, regulators will need to ask banks to publish even better data.
Keywords: F21; F23; G21; G28; H25; H87; 330; country-by-country reporting; banks; tax havens; profit shifting; financial transparency; European Union